(untitled) (Pulse, 2014)
Extended spectrum ?-lactamase (ESBLs), produced by Gram negative organisms, are enzymes capable of hydrolyzing extended spectrum cephalosporins, penicillins and monobactam but inactive against cephamycin and imipenem. Detection of some ESBL strains are missed by Double disc synergy test but detected by three dimensional test. So this study was carried out to see the rate of ESBL producer by three dimensional test and double disc synergy test among Gram negative bacteria. Total 110 Gram negative isolates were studied, among them 30 were wound swab isolates and 80 were laboratory isolates, of which 88(80%) were ESBL producer. Three dimensional tests detected ESBL in 88 (80%) strain whereas 66.36% strains detected by double disc synergy test, so 15 (13.63%) isolates were missed by Double disc synergy test. In this study among the 30 wound swab isolates Three dimensional test detected 26 (86.67%) whereas 14 (46.67) were detected by double disc synergy test and similarly among the 80 laboratory isolates, three dimensional test detected 62 (77.5%) and double disc synergy test detected 59 (73.75%). So, the three dimensional test has been found to be better than Double disc synergy test in the detection of ESBLs. ESBL producing organisms are resistance to most of the antibiotics but 100% sensitive to Imipenem. DOI: http://dx.doi.org/10.3329/pulse.v6i1-2.20328 Pulse Vol.6 January-December 2013 p.12-19